Mobile-Assisted Language Learning (MALL) for Indonesian EFL Learners: Enhancing Vocabulary Through Gamified Apps - Ming Pong; Rit Som; Vann Sok (Yayasan Adra Karima Hubbi, 2025)
Background. Rapid technological advancement has reshaped English language teaching, prompting the integration of mobile-assisted language learning (MALL) as a dynamic medium for vocabulary acquisition. In Indonesia, where English is a foreign language (EFL), learners often struggle to retain vocabulary due to limited exposure and traditional memorization-based methods. Purpose. This study investigates the effectiveness of gamified mobile applications in enhancing Indonesian EFL learners’ vocabulary mastery within the MALL framework Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. Data were collected through pre- and post-tests, learner attitude questionnaires, and semi-structured interviews. Statistical analysis using paired-sample t-tests revealed a significant improvement in vocabulary scores of the experimental group compared to the control group (p < .05). Qualitative findings further indicated that gamification fostered higher motivation, self-efficacy, and autonomous learning behaviors.. Conclusion. The study concludes that integrating gamified MALL platforms effectively bridges linguistic and motivational challenges among Indonesian EFL learners, providing a sustainable alternative to traditional instruction. These findings underscore the pedagogical potential of mobile technology to support vocabulary development and learner engagement in digitally enriched learning environments.